Adjuvant Chemotherapy in Colon Cancer: Simple is Better… Less is More - Narayanan, Prasad; Aggarwal, Shyam; Singhal, Manish; Krishna, Vamshi; Rathi, A. K.; Singh, Brig H. P.; Sharma, Atul; Sharma, J. B.; Bhargava, Amit; Suresh, P.; Walia, Meenu; Darling, H. S.; Medhi, K.; Dutta, Kumardeep; Rajpurohit, Sajjan Singh; Mehta, Prashant; Goswami, Vikas; Rawat, Saumitra; Selvasekar, C.; Parikh, Purvish M. (South Asian Journal of Cancer, 2024)
A significant number of patients with colorectal cancer (CRC) benefit from adjuvant therapy. While 6 months of FOLFOX is standard of care, newer regimens like CAPOX and SOX allow for shorter durations. Trials of importance include SCOT (U.K., Denmark, Spain, Sweden, Australia, New Zealand), TOSCA (Italy), Alliance/SWOG80702 (U.S., Canada), IDEA (France), ACHIEVE (Japan), and HORG (Greece). Management recommendation is also based on patient preferences, dividing them into fighters and fatalists. Better patient selection is possible with the use of novel molecular-based biomarkers and circulating tumor deoxyribonucleic acid monitoring of minimal residual disease. There also needs to be special consideration for the geriatric patients—especially due to their limited mobility, comorbidities, and polypharmacy.
Keywords: overall survival; toxicity; drug metabolism; geriatric patients; ctDNA; MRD